Educational Strategic Planning In Dayah Modern Darul Ulum Banda Aceh Through The Corporate Social Responsibility (CSR) Program - Ansari, Ismail; Lita Sari, Wahyu; Hadi, Abdul (Jurnal Al-Fikrah, 2023)
Competition between educational institutions is currently increasingly tight, this requires madrasas to continue responsible answer in educational strategic planning . This research was conducted at MTs Darul Ulum. The purpose of this research is first, how to plan the Corporate Social Responsibility program, second, to find out the implementation of the Corporate Social Responsibility program and third, to find out the evaluation of the Corporate Social Responsibility program. This research is qualitative research using observation, interview and documentation techniques in data collection. Subject research This is madrasa head master, treasurer, teachers and students. Data analysis uses triangulation theory as a technique for checking the validity of the data by comparing the results of interviews and observations to check the correctness of the data. The results of the research show that, firstly, planning the Corporate Social Responsibility program involves the madrasah, especially the head of the madrasah, to prepare the program that will be carried out, determine the targets in the program, determine the time period for implementation and the person responsible for each program that will be carried out. Secondly, the implementation of the Corporate Social Responsibility program is carried out by providing guidance and training for teachers (employees) so that the planned program can be carried out in accordance with the directions. Third, evaluation of the Corporate Social Responsibility program in educational strategic planning at MTs Darul ՚ Ulum Banda Aceh head of the madrasah conducted an evaluation to assess what programs needed to be improved (whether the program was running or not).